Do psychosocial job stressors differentially affect the sleep quality of men and women? A study using the HILDA Survey. (8th May 2021) - Scovelle, A J; King, T; Shields, M; O'Neil, A; Lallukka, T; Hewitt, B; Milner, A
Abstract: The aim of this study was to investigate whether gender was an effect modifier of the relationship between three psychosocial job stressors and sleep quality, in a representative sample of 7280 employed Australians. We conducted linear regressions and effect measure modification analyses. Low job control, high job demands and low job security were associated with poorer sleep quality. There was evidence of effect modification of the relationship between job security and sleep quality by gender on the additive scale, indicating that the combined effect of being male and having low job security is greater than the summed interactive effect.